2013
DOI: 10.1161/circinterventions.112.000324
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Steerable Robotic Tool Delivery Platform and Metal Microelectromechanical Systems Device for Tissue Manipulation and Approximation

Abstract: Background Beating-heart image-guided intracardiac interventions have been evolving rapidly. To extend the domain of catheter-based and transcardiac interventions into reconstructive surgery, a new robotic tool delivery platform (TDP) and tissue approximation device have been developed. Initial results employing these tools to perform patent foramen ovale (PFO) closure are described. Methods and Results A robotic TDP comprised of superelastic metal tubes provides the capability of delivering and manipulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…However, tracking was limited to one degree-of-freedom (DOF) in that study. Vasilyev et al demonstrated a percutaneous steerable robotic tool delivery platform using pre-bent concentric tubes robot to treat patent foramen ovale [16]. Although the pre-bent concentric tubes robot could be adapted for valve delivery using transapical access, the design provides limited capabilities to compensate for respiratory and beating heart motions.…”
Section: Introductionmentioning
confidence: 99%
“…However, tracking was limited to one degree-of-freedom (DOF) in that study. Vasilyev et al demonstrated a percutaneous steerable robotic tool delivery platform using pre-bent concentric tubes robot to treat patent foramen ovale [16]. Although the pre-bent concentric tubes robot could be adapted for valve delivery using transapical access, the design provides limited capabilities to compensate for respiratory and beating heart motions.…”
Section: Introductionmentioning
confidence: 99%
“…Active shape change is achieved by relative rotation and translation of the tubes at their base. Since they can be constructed with diameters similar to those of catheters and yet offer greater stiffness combined with the capability of shape control along their entire length, they provide an effective tool delivery technology for reconstructive procedures inside the beating heart (Gosline et al, 2012a(Gosline et al, , 2012bVasilyev et al, 2012Vasilyev et al, , 2013.…”
Section: Engineering Challengesmentioning
confidence: 99%
“…The approach has been validated with in vivo large animal experiments, which demonstrated a novel alternative to both catheter-delivered PFO closure devices and to surgical closure by suture (Gosline et al, 2012a;Vasilyev et al, 2013). This paper considers the task of tissue removal inside the beating heart.…”
Section: Clinical Significancementioning
confidence: 99%
“…Path planning algorithms are also being developed to enable robot navigation within anatomical constraints [13], [18]. Clinical applications considered to date include neurosurgery [7], [19], lung surgery [13], [14], [18] and cardiac surgery [1], [15], [16], including in vivo demonstrations of percutaneous beating-heart intracardiac surgery in an animal model [16], [20]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the neurosurgical example solves for a robot design that can safely navigate through both ventricles from a single insertion point while prior designs were constrained to navigating within a single ventricle [7]. We have also added an experimental validation of a robot design for intracardiac PFO closure by comparing it against a robot successfully employed in beating-heart procedures [16], [20]. …”
Section: Introductionmentioning
confidence: 99%